Identifying ovarian cancer with machine learning DNA methylation pattern analysis - Jesus Gonzalez Bosquet; Vincent M. Wagner; Douglas Russo; Henry D. Reyes; Andreea M. Newtson; David P. Bender; Michael J. Goodheart (Scientific Reports)
Abstract The majority of patients with epithelial ovarian cancer (EOC) continue to be diagnosed at an advanced stage despite great advances in this disease treatment. To impact overall survival, we need better methods of EOC early diagnosis. We performed a case control study to predict high-grade serous cancer (HGSC) using artificial intelligence methodology and methylated DNA from surgical specimens. Initial prediction models with MethylNet were accurate but complex (AUC = 100%). We optimized these models by selecting the most informative probes with univariate ANOVA analyses first, and then multivariate lasso regression modelling. This step-wise approach resulted in 9 methylated probes predicting HGSC with an AUC of 100%. These models were validated with different analytics and with an independent DNA-methylation experiment with excellent performances.